2013 National Turfgrass Evaluation Program Bermudagrass Test - L. Parsons; J. Griffin; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2015)
Kansas represents the northernmost region in the central United States where bermudagrass can be successfully grown as a perennial turfgrass. Historically, few cultivars that have both acceptable quality and adequate cold-tolerance have been available to local growers. Because new introductions are continually being selected for improved hardiness and quality, both seeded and vegetative types need regular evaluation to determine their long-range suitability for use in Kansas.
Keywords: bermudagrass; National Turfgrass Evaluation Program; NTEP